Penyusunan Anggaran Operasional pada UMKM Tahu XYZ Cabang Sako Palembang - Wulan Suci Sektia Ningrum; Marieska Lupikawaty; Yulia Pebrianti (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This research aims to prepare an operational budget for MSMEs Tahu XYZ Sako Palembang Branch as an effort to control costs and effective financial planning. Budget preparation is considered important because it can be a tool of managerial control, a means of evaluation, as well as a basis for decision-making that supports business sustainability. The research method used is quantitative descriptive with a case study approach. Data was obtained through interviews with owners and employees, direct observation of production activities, and documentation of financial statements. Secondary data in the form of MSME financial records for the period 2022 to 2024 were also analyzed to produce a comprehensive picture of the company's condition. The results of the study show that so far MSMEs have not prepared operational budgets in a structured manner, making it difficult to monitor financial conditions and performance thoroughly. After preparing the budget, it was found that the selling price of the product was lower than the production cost, causing a loss of IDR 5,028,927 in 2025. The budget also shows that the burden of non-production costs, such as marketing and distribution costs, is quite high and needs to be controlled. On the other hand, the results of interviews with consumers show that the majority are willing to accept an increase in the selling price of products as long as the quality is maintained, the service does not decrease, and the added value is still felt. These findings confirm that the preparation of operational budgets is an important instrument in supporting cost efficiency, determining the right selling price, and the sustainability of MSMEs.